PowerShell in practice - Siddaway, Richard (Manning, 2010)
"Windows PowerShell is a scripting language that simplifies Windows system administration. PowerShell in Practice is a hands-on reference for administrators wanting to learn and use PowerShell. Following the 'in Practice' style, individual related techniques are clustered into chapters. Each technique is presented in the form: problem, solution, discussion, and includes annotated code listings. Written to answer the question 'How can PowerShell make my job as an administrator easier?' this book concentrates on practical tasks and automation. Starting with an a brief tutorial and review, the majority of the book focuses on two major PowerShell usage areas: People - user accounts, mailboxes, desktop configuration; and Servers - Active Directory, Exchange, IIS, and more"--Resource description page.
Print version record
Keywords: Microsoft Windows (Computer file); Windows PowerShell (Computer program language); Command languages (Computer science); Scripting languages (Computer science); Systems programming (Computer science); Windows PowerShell (Langage de programmation); Langages de commande (Informatique); Langages de script (Informatique); Programmation système (Informatique)